2022
DOI: 10.3390/jcdd9020032
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) Does Not Affect Outcome in Patients with Acute Myocarditis or Myopericarditis

Abstract: Background: Previous animal studies reported an association of non-steroidal anti-inflammatory drugs (NSAIDs) with adverse outcomes in acute myocarditis, which is why these drugs are currently not recommended in affected patients. In this retrospective case-control study, we sought to investigate the effects of NSAID treatment in patients with acute myocarditis and myopericarditis to complement the available evidence. Method: A total of 114 patients with acute myocarditis were retrospectively enrolled. Demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Treatment with non-steroidal anti-inflammatory drugs (NSAIDs) in myopericarditis is another unsolved problem. There are studies supporting the hypothesis that it can be potentially harmful and should be avoided in myocarditis [ 102 ], as well as studies where NSAIDs neither affected all-cause mortality rate nor left ventricle function [ 103 ]. Nevertheless, none of the studies showed the benefit of NSAIDs in myocarditis treatment, and generally, they should not be widely implemented [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with non-steroidal anti-inflammatory drugs (NSAIDs) in myopericarditis is another unsolved problem. There are studies supporting the hypothesis that it can be potentially harmful and should be avoided in myocarditis [ 102 ], as well as studies where NSAIDs neither affected all-cause mortality rate nor left ventricle function [ 103 ]. Nevertheless, none of the studies showed the benefit of NSAIDs in myocarditis treatment, and generally, they should not be widely implemented [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our patient was initially treated with a high dose of MP: 2 mg/kg/day (with the possible implication of early-started low-dose corticosteroids due to rash and concern of an allergic reaction), and the high dose was reduced to a moderate dose (0.3 mg/kg/day) after TTE and laboratory confirmation of myocardial recovery with further gradual dose reduction. Ibuprofen was stopped since non-steroidal anti-inflammatory drugs (NSAIDs) could enhance inflammation and increase mortality, which has been shown in animal models of myocarditis, although recent findings suggest that treatment with NSAIDs does not affect outcome in patients with acute myocarditis or myopericarditis [10,11,16]. In our opinion, patients with HF due to SLE should be treated in parallel with HF guidelinedirected therapy to reduce the risk of further myocardial damage and potential complications, although the optimal duration of the treatment is not yet well-established.…”
Section: Discussionmentioning
confidence: 99%
“…The use of NSAIDs on humans with myocarditis still lacks supporting evidence. Animal studies show they aggravate myocardial inflammation and necrosis, elevate viral titers, and reduce interferon [ 2 , 17 ]. About 50% patients made a full recovery, some developed heart failure (30%), and about 20% required heart transplantation [ 5 ].…”
Section: Discussionmentioning
confidence: 99%